1989
DOI: 10.2136/sssaj1989.03615995005300020008x
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Extraction Procedure with Concentrated Sulfuric Acid and Dilute Base for Soil Organic Phosphorus

Abstract: A total soil organic P (TPo) method that retains the relative ease of the dry combustion method and still preserves essentially all organic P in the extract would be desirable. A sequential extraction procedure for TPo with concentrated sulfuric acid and dilute base was therefore developed to meet these objectives. The method was based on the high efficiency of Po extracted from soils by the heat of solution created by addition of water to concentrated H2SO4. In this step of the procedure, 79% of the total Po … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
27

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(121 citation statements)
references
References 0 publications
1
89
0
27
Order By: Relevance
“…O Po total foi obtido por meio do método de extração seqüencial (Bowman, 1989), e o Po lábil, pelo método de extração com NaHCO 3 0,5 mol L -1 (Bowman & Cole, 1978). O Pi foi determinado após clarificação dos extratos com carvão ativo (Guerra et al, 1996).…”
Section: Methodsunclassified
“…O Po total foi obtido por meio do método de extração seqüencial (Bowman, 1989), e o Po lábil, pelo método de extração com NaHCO 3 0,5 mol L -1 (Bowman & Cole, 1978). O Pi foi determinado após clarificação dos extratos com carvão ativo (Guerra et al, 1996).…”
Section: Methodsunclassified
“…Organic matter was first precipitated by acidification in the bicarbonate and the NaOH extracts before P i determination (Tiessen & Moir, 1993). Total P in the bicarbonate, the NaOH and the HCl extracts was measured after digestion of extracts with potassium persulfate (Bowman, 1989). Organic P was calculated as the difference between total P and P i in the bicarbonate, NaOH and hot HCl extracts.…”
Section: Soil Analysismentioning
confidence: 99%
“…The WC litter and litter-treated soil were incubated for 43 days and sampled after 0, 15, 22, 29, 36, and 43 days to monitor the P transformation kinetics. The collected samples were chemically fractionated (Bowman, 1989) into inorganic (Pi) and organic phosphorus (Po) fractions. The change in Pi and Po was calculated as the difference in P forms during the incubation period and the rate of P mineralization was calculated from the percentage increase in Pi during incubation per unit of Po.…”
Section: Experiments 1 Phosphorus Transformation In Poultry Litters Ementioning
confidence: 99%
“…The chemical fractionation of litter using Bowman's fractionation scheme (Bowman, 1989) revealed that the concentration of Pi was higher in the RH litter and lowest in the CH litter, but did not differ from Pi in the WC and CC litters (Table 3). The same pattern was observed for the Po concentration.…”
Section: Soil-litter Incubation Study: Chemical Fractionationmentioning
confidence: 99%
See 1 more Smart Citation